Poetiks of L. Andreev’s play «Black masks» - Сухоруков, Виктор Анатольевич (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
In article is devoted to the thorough analysis of poetics and genre peculiarities of L. Andreev’s play «Black masks». The investigation showed that the important role in this work play modernistic principles of representation of world and person as neomythologism, intertextuality, motifity, dominating of symbolical types and characters, irony, grotesque. This is the "new drama" which moves to the scene external conflict and the action, and the key role is played by internal conflict and subtext, which is finding realization in neomifological storyline. The original model established by L. Andreev in the first dramas was invariant and only varied in subsequent plays.